Emisiones diurnas y nocturnas de CH4 y N2O en la turbera de Quistococha en Loreto, Perú, 2021 - Peas García, Edgar (2022)
The study was conducted in the peatlands of the Quistococha – Iquitos Zoo. The objective was to estimate the daily cycle of CH4 and N2O gas flows in relation to the environmental variables of the Quistococha peatland in Loreto – Peru; where, the closed chamber methodology (typically <1m2) was used, which consists of measuring the flow of trace gases of CH4 and N2O (Hutchinson and Livingston, 1993). The daily cycles of the CH4 flow in the Peatland of Quistococha, during the first and second campaign presented an average of 2407,9 and 2154,5 (?g-C/m?2/h?1), respectively. Likewise, N2O presented a daily average of 37,3 and 5,4 (?g-N/m?2/h?1), respectively. It was observed that there are slight differences in the flows of CH4 and N2O gases between day and night, being greater during the day the average flow of CH4, first campaign (2576,33 and 2239,49 ?g-C/m?2/h?1, respectively) and second campaign (2446,36 and 1862,59 ?g-C/m?2/h?1, respectively) constantly, and inconsistently in relation to the average flow of N2O, first campaign (40,69 and 33,85 ?g-N/m?2/h?1, respectively) and second campaign (4,87 and 5,36 ?g-N/m?2/h?1, respectively), but no significant differences were found with respect to the different shifts (day and night), nor between the different times of the day, according to Wilcoxon and kruskal wallis tests, respectively. The environmental variables of soil temperature, photosynthetically active radiation and water table do not significantly influence the daily flow of CH4 and N2O in the Quistococha peatland, according to the spearman test, since they presented low and null correlations.